A Project feasibility study wire boxes - Arabit, Ma. Abigail A. (College of Engineering, 1993)
Mealmint Trading, Incorporated is an existing company which manufactures wire boxes for export. The company entered the present market based on "gut feeling". No effort was done to systematically plan the venture. The market was not clearly identified, a conventional and simple method of production was used, and the financial aspect of the venture was not explored. As the company received more orders for its products, there was a need to establish a feasibility study to determine the company's present position in the market, the corresponding technical aspect of production needed to produce the demand for the company's product, and the financial resources necessary for the company's operations. This feasibility study is composed of three major parts: the market, technical and financial studies. Mealmint does not know its position in the market and cannot clearly identify its customers. Customers are limited in that they are the people who by chance knows of Mealmint. The company has no marketing plan in order to make its product known. The project team then conducted a market study. The results of the market study reveals that there is an increasing trend on the export of brass/metal items, under which the wire boxes are classified. research also revealed ten countries which have been the top importers of Philippine metal/brass items for the last five years. Most of theses countries are located in North America and in Europe. These ten countries can be tapped as the potential customers of the company. Based on the value of the 1992 Philippine exports of brass/metal items, the market share of the company was also determined. The project team forecasted the demand for Philippine exports of brass/metal items for the next five years. And from the forecasted demand, the demand for the wire boxes was established using the market share of Mealmint, which was targeted to increase at the rate of 0.5% every year. The forecasted demand of wire boxes reveals that the demand is increasing. The project team was then able to conclude that there is a feasible market for wire boxes. The market study was followed by a technical feasibility study to determine the technology that will enable the company to produce the demand for its product. After analyzing several alternatives, the project team was able to propose a new method of production which will increase the company's output so that the appropriate amount of demand can be produced. The main point of the technical study was the proposal of the use of furnace brazing as a soldering method in combination with the conventional method of soldering using the soldering iron in the assembly of the wire box. Other proposals include the use of soldering aids, fixtures, and a designed foot driven bending machine to form wires into their desired shapes. A corresponding production plan and a production program was also presented. The result of the technical study indicate that the project is feasible. The projected demand from the market study can be supported and produced by the method of production presented in the technical study. A financial study was then conducted by the project team in order to determine the amount of resources needed for the project and its profitability. P 1,000,000 will be financed through borrowing and the rest of the required project cost will be provided for by the owner of the company. The study reveals that Mealmint will immediately gain profit after the first year of its operation. However, the profit is not too high. But in the next few years of operation, the company will gain large profits and will be able to pay its loan in four years. Hence, it was concluded by the project team that the project is financially feasible. A social profitability study was also conducted by the project team. The study reveals that the project is in lie with the national objectives. The project can generate jobs, contribute to foreign exchange savings, develop the export market, and use local materials. The result of the study indicates that the project is socially profitable. Considering all aspects (market, technical, financial and social profitability studies), the project on the production of wire boxes is feasible.